Printing the light. (24th January 2021) - Parraman, Carinna; Klein, Susanne
Abstract: This paper explores the relationship between additive and subtractive mixing for colour printing. Using Spectraval mica pigments (Merck)—marketed as RGB pigments—colour is generated by selective reflection and prints are based on additive colour mixing principles, that when printed onto black paper, create white and a range of colours. Although currently used mostly for decorative effects, they can be the basis of additive 'process' inks, that present new opportunities for and challenges to traditional print markets. The viewing angle dependency of their selective reflection favours applications in security printing similar to the holograms on bank cards for example. Traditional measurement and modelling methods are difficult to apply due to the layering and irregular dispersion of pigments.